Aplikasi modul belajar melaui bermain dalam kefahaman awal matematk dan motivasi kana-kanak prasekolah - Mohamad Ashari, Zakiah (2014)
The purpose of this research is to identify the effectiveness of using learning through play module on preschool children’s understanding and motivation in the prenumber experience and number concept topics. This research also examined the perceptions of preschool teachers on teaching and learning process using learning through play module. Aligned with this research purpose, a learning through play module that emphasizes on socio-cognitive play (functional play, constructive play, dramatic play and play with rules) was developed. This module is implemented through the quasi-experimental research design involving four preschools under the Ministry of Education in Johor. A total of two preschools were placed in experimental group and the other two preschools were placed in the control group. This study used three methods of data collection namely prenumber experience and number concept understanding test, motivation questionnaire and protocol interview. Data were analyzed using paired samples t-test and Wilcoxon Signed-rank test. The analysis of prenumber experience and number concept understanding test showed a significant increase on children’s understanding in the experimental group and control groups. However, the difference between the means in the experimental group was higher than in the control group. Similar result has been found for motivation. The analysis of motivation questionnaire showed significant increases between the pre-post mean scores of the experimental group and control group. However, the difference between the mean scores of motivation in the experimental group was higher than the control group. Qualitative data analysis found that both preschool teachers from the experimental group gave a positive perception towards learning through play module that has been implemented. The results showed that the teaching and learning process using learning through play module in two preschools managed to create a structured and systematic learning environment, thus helping to improve the children’s motivation and understanding of prenumber experience and number concept. Therefore, this module should become a guide especially for Ministry of Education preschool teachers in early mathematics teaching using learning through play approach.